2021
DOI: 10.5751/es-12265-260222
|View full text |Cite
|
Sign up to set email alerts
|

Fostering horizontal knowledge co-production with Indigenous people by leveraging researchers' transdisciplinary intentions

Abstract: Transdisciplinarity involves knowledge co-production with non-academics. This co-production can be horizontal when equal consideration is given to the contributions from different knowledges and ways of knowing. However, asymmetric power relations and colonial patterns of behavior, which are deeply rooted in academic culture, may hinder horizontality. Using Icek Ajzen's Theory of Planned Behavior, we elicited and analyzed the attitudes, perceptions, and behavioral intentions towards knowledge co-production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Finally, transdisciplinary research can be understood as knowledge production that either transcends different disciplines (Max-Neef, 2005;Heinzmann et al, 2019), or that transcends the disciplines to work with non-academics (Uiterkamp and Vlek, 2007;Manuel-Navarrete et al, 2021). In their review of 59 sustainability-focused completed research projects, Jahn et al (2021) found a spectrum of different forms of transdisciplinarity among a diversity of research approaches that reveal five different research modes with different approaches and outcomes.…”
Section: Defining Transdisciplinaritymentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, transdisciplinary research can be understood as knowledge production that either transcends different disciplines (Max-Neef, 2005;Heinzmann et al, 2019), or that transcends the disciplines to work with non-academics (Uiterkamp and Vlek, 2007;Manuel-Navarrete et al, 2021). In their review of 59 sustainability-focused completed research projects, Jahn et al (2021) found a spectrum of different forms of transdisciplinarity among a diversity of research approaches that reveal five different research modes with different approaches and outcomes.…”
Section: Defining Transdisciplinaritymentioning
confidence: 99%
“…a process of joint knowledge production characterized by the inclusion of scientific and non-scientific perspectives and real-world practice (Schreiber et al, 2022) "focus on transcending [academic] disciplines and engagement with external stakeholders" (Benham and Daniell, 2016). "knowledge co-production with non-academics" (Manuel-Navarrete et al, 2021).…”
Section: Transdisciplinary Researchmentioning
confidence: 99%
See 3 more Smart Citations